Los otros - Almenábar, Alejandro; Kidman, Nicole, 1967- (Madrid Mercury Films, 2001)
A woman who lives in a darkened old house with her two photosensitive children becomes convinced that her family home is haunted.
Nicole Kidman, Christopher Eccleston, Fionnula Flanagan
No recomendada para menores de 13 años.
Idiomas: español, inglés ; subtítulos en español, inglés
Keywords: Películas cinematográficas -- DVD